A Comparative Study on Effect of Oral Administration of Turmeric and Nutmeg on Memory Boosting and Regaining in Wistar Albino Rats - Kumar, SS; Jissa, G; Setty, PV; Mukkadan, JK (Journal of Universal College of Medical Sciences, 2013)
BACKGROUND AND OBJECTIVES: Although a few drugs are available today for the management of Alzheimer's disease (AD) and many plants and their extracts are extensively employed in animal studies and AD patients, yet no substantial drug or plant extract is able to reverse the AD symptoms adequately. It is tangible that there has been augmenting need for such therapeutic intervention. The present study was undertaken with an objective to compare the memory boosting and regaining effects of oral administration of nutmeg and turmeric which are used commonly as spice in various dishes, as components of teas and soft drinks. MATERIAL AND METHODS: A total of 24 male and female wistar albino rats were used for this study. They were randomly assigned into three groups with 8 rats in each group. The influence of oral intake of nutmeg and turmeric extract on behavioral task performance was studied by using T-maze and radial arm maze and physiological measures relative to a milk control group was investigated. RESULTS: We have observed significant memory boosting and memory regaining effects of nutmeg when administered orally when compared with control group..However, nutmeg is having strong memory regaining effect than turmeric. CONCLUSION: We conclude that nutmeg is having strong memory regaining effect than turmeric. However further pharmacological and biochemical investigations will clearly elucidate the mechanism of action and helpful in projecting these plant extracts as a therapeutic target in diabetes research. DOI: http://dx.doi.org/10.3126/jucms.v1i3.8765 Journal of Universal College of Medical Sciences Vol.1(3) 2013: 46-52